Assessing learning outcomes through students’ reflective thinking - Ho, Yuek Ming; Abdul Manaf, Latifah (Elsevier, 2014)
Assessing students’ reflective thinking could reveal learning outcomes which summative assessment could not. Therefore, the researcher as course instructor decided to look into students’ reflective writing for a more insightful feedback on their learning outcomes. One cohort of students in an environmental management course were requested to write reflection notes at the completion of each assignment, and towards the end of the course a piece of reflective essay. The students’ reflective writings were then analysed for snippets of evidence that purportedly meets the course learning outcomes. These evidences of students’ learning outcomes were gathered and examined for emerging patterns and trends in the students’ reflective thinking that relates to the course objectives. The document analysis method was applied to identify and match the students’ reflective writings with the learning objectives. Findings reveal students’ achievement of learning outcomes and higher order thinking skills, as outlined in the course objectives. It is hoped that findings from this research will further support the significance of reflective thinking on learning. Reflective notes provide meaningful feedback on learning to instructors that could be acted upon towards improvement of a course. Educators and educationists could look at students’ reflective writings as an effective form of assessment that would provide a more insightful assessment of students’ learning and thoughts.